Perencanaan Rumah Panggung, Maskot Bundaran dan Peta di Desa Tuwung Pulang Pisau, Provinsi Kalimantan Tengah - Dina Titania; Joshua Willy Arista W. Usup; Moses Prasaktiyadsi; Alprido Perdian; Miguel Fernando Marpaung; Rara Fahriyanti; Herna Wati Lumbantobing; Irfan Hagata Tarigan (Fakultas Teknik Universitas Palangka Raya, 2026)
The Teknik Membangun dan Berdampak (TMB) Program 2025 is a community service activity conducted in Tuwung Village, Kahayan Tengah District, Pulang Pisau Regency. This program is motivated by the need for rural infrastructure development that supports social functions, tourism potential, and the strengthening of local identity. The objective of this activity is to develop planning designs for a stilt house, a village roundabout mascot, and a village area map to support sustainable rural development. The methods used include field surveys, collection of topographic, spatial, and socio-cultural data, as well as participatory discussions with the community and village government. The data were processed to produce a Detailed Engineering Design (DED), Cost Budget Plan (RAB), and village map using QGIS 3.40 software. The results indicate that the stilt house is designed to adapt to peatland conditions with both social and tourism functions, the roundabout mascot represents local identity through the rambutan symbol, and the village map provides informative and accurate spatial information. This planning is expected to serve as a technically feasible reference and support the achievement of the Village Sustainable Development Goals (SDGs).